Progressing towards adolescent ovulatory menstrual health literacy: a systematic review of school-based interventions - Roux, Felicity; Burns, Sharyn; Hendriks, Jacqui; Chih, Jun (2021)
This study was designed to evaluate the extent to which school-based ovulatory-menstrual (OM) health interventions facilitate the Health Outcome Model’s domains of health literacy. Electronic databases and gray literature sources were searched from 1980 to 2019. Findings from 16 studies of school-based OM health interventions (n = >8800 adolescents aged 13–16 years) were collated. The results indicate that OM health education addresses the domains of health literacy to various degrees; critical health literacy skills are least often addressed. Future programs would benefit from positive teaching about the cycle as a health monitor and from engaging parents and healthcare providers.